Stereoscopic optical palpation for tumour margin assessment in breast-conserving surgery. (July 2023) - Fang, Qi; Choi, Seokhyun; Taba, Aiden; Lakhiani, Devina D.; Newman, Kyle; Zilkens, Renate; Sanderson, Rowan W.; Dessauvagie, Benjamin F.; Saunders, Christobel M.; Kennedy, Brendan F.
Highlights: A novel camera-based optical palpation technique, stereoscopic optical palpation (SOP), is developed in this paper, demonstrating a high strain sensitivity of 4.2 mε. A novel dichroic silicone layer with embedded phosphorescent microparticles is developed to allow sequential acquisition of stress maps and visible-light photographs of tissue, providing accurate image co-registration. SOP is performed on freshly excised human breast tissue, demonstrating the capability to generate mechanical contrast and to identify tumour at the surgical margins. Abstract: Optical palpation is an emerging set of techniques that utilise an optical imaging system to generate images of mechanical contrast in tissue with micro- to milli-scale resolution. Recently, digital cameras have been proposed as the imaging system, due to their affordability and portability, realising cost-effective and rapid tissue assessment. Despite these benefits, existing camera-based optical palpation techniques use indirect strain estimation approaches and it is not possible to acquire both photographs and stress maps of the tissue, resulting in low strain sensitivity (∼100 mε) and inaccurate co-registration with tissue features. In this paper, we propose a new camera-based optical palpation system, termed stereoscopic optical palpation (SOP) that exploits stereoscopic imaging from two parallel cameras to directly map the strain of a compliant layer that is placed on top of the tissue. Stress maps are then generated from the measured strain and the pre-characterised mechanical properties of the layer, providing images with mechanical contrast derived from the elasticity of the underlying tissue. Using SOP, we demonstrate a strain sensitivity of 4.2 mε, a 24-fold improvement over previous camera-based optical palpation techniques. In addition, by embedding phosphorescent microparticles in the compliant layer, we demonstrate sequential acquisition of stress maps and visible-light photographs under different illumination conditions, providing accurate image co-registration between features in the stress map and the visual position on the tissue surface. We perform SOP on silicone phantoms and freshly excised human breast specimens. We compare SOP images with OCT-based optical palpation and histology for validation, demonstrating its capability for rapid and reliable imaging and the potential for tumour margin assessment in breast-conserving surgery.